Mengembalikan Pola Transmisi Pembelajaran Pendidikan (Islam) di Kelas yang Dianggap Tidak Efektif oleh Dunia Sekuler Melalui Manhaj Rasul - Yulianti, Eva (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
This paper aims to describe how to restore the transmission pattern of educational learning (Islam) in the classroom which is considered ineffective by the secular world through Manhaj Rasul. This research is a qualitative literature study to provide a set of insights into how phenomenons are interpreted in the literature. Research design becomes a reflexive process at every stage of the research. Qualitative analysis uses comparisons made between different types of organizations in terms of structure, culture, size, the like and characteristics observed to study the larger unit of analysis. From the results of the discussion, it can be concluded as follows: 1) Islamic education which was officially started by the Prophet Muhammad when he received the first revelation (Qs. Al 'Alaq [96]: 1-5) and continued the second (Qs. Al Muddatstsir [74]: 1-7) and strengthened by the decline (Surah Al Hijr [15]: 94-95) regarding Islamic education, it is time to go international through the hajj activities in the 12th year of prophecy. 2) As a result of the influence of the Qur'anic revelation as well as other factors related to the rise of the Islamic education system as a whole, the oral dimension of the Qur'anic reality, combined with the significance of memory in the transmission of knowledge, was able to influence the entire intellectual tradition and the Islamic education system. 3) The pattern of early Islamic education with minimal facilities, but the output of the results of its education to be the best generation in history, over time it began to be abandoned and even considered ineffective.